Nano Science and Technolgy
DOI: 10.1007/978-3-540-74083-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy: Interaction Forces Measured in Phospholipid Monolayers, Bilayers and Cell Membranes

Abstract: Atomic force microscopy (AFM) is a powerful technique which is commonly used to image surfaces at the nanoscale and single-molecule level, as well as to investigate physical properties of the sample surface using a technique known as force spectroscopy. In this chapter, we review our recent research where we used AFM to investigate physical properties of phospholipid monolayers, bilayers, and cell membranes. We describe the experimental procedures for AFM imaging, force measurements, and theoretical models to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…Strictly speaking, the Reissner approximation is only valid where the loading of the MB is point-like, however Elsner et al [52] showed by AFM force spectroscopy measurements of polymeric shells in conjunction with finite element analysis the theory can be applied to systems having non-point like loads and over large contact areas. The Reissner solution has been used in studies on polymer microbubbles, [48,53] microcapsules [48,53,54] and phospholipid vesicles, [55,56] when a linear relation was observed at the initial stage of the F-Δ curves.…”
Section: Reissner Approximationmentioning
confidence: 99%
“…Strictly speaking, the Reissner approximation is only valid where the loading of the MB is point-like, however Elsner et al [52] showed by AFM force spectroscopy measurements of polymeric shells in conjunction with finite element analysis the theory can be applied to systems having non-point like loads and over large contact areas. The Reissner solution has been used in studies on polymer microbubbles, [48,53] microcapsules [48,53,54] and phospholipid vesicles, [55,56] when a linear relation was observed at the initial stage of the F-Δ curves.…”
Section: Reissner Approximationmentioning
confidence: 99%
“…Some smaller molecules, such as carbon dioxide and oxygen, can pass through without difficulty on their own, but larger molecules such as water, sodium, or magnesium cannot pass easily [ 13 ]. The interior of the membrane is also liquid, and this lets proteins, cholesterol, sphingolipids, or sterols converge in it.…”
Section: Introductionmentioning
confidence: 99%
“…The interior of the membrane is also liquid, and this lets proteins, cholesterol, sphingolipids, or sterols converge in it. The role of sphingolipids is to protect the outside of the cell, and the role of the sterols and cholesterols is to stabilize the phospholipid bilayer in plant and animal cells, respectively [ 13 ]. Although this is critical for cells to have enough constancy, a large amount of cholesterol can make them inflexible, which is hazardous especially if they are part of a vein that must be flexible to allow blood flow [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Normally there is water both outside and inside the cells, hence the molecules form themselves between two sheets, with the hydrophobic ends of both layers in inward direction and the hydrophilic ends of them pointing outwards. 1618…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Normally there is water both outside and inside the cells, hence the molecules form themselves between two sheets, with the hydrophobic ends of both layers in inward direction and the hydrophilic ends of them pointing outwards. [16][17][18] A key role of phospholipid bilayer is to prepare the structure to a cell. This is achieved when the hydrophobic and hydrophilic ends of phospholipids are naturally arranged, and when stable, cholesterol and sterols contribute to this too.…”
Section: Introductionmentioning
confidence: 99%